Mampukah sekolah gratis mencapai pemenuhan standar nasional pendidikan? - Rahman, Abdul; Nasihin, Ahmad (Ta’dibuna: Jurnal Pendidikan Islam, 2020)
Politically, the policy of free schooling is interesting but in implementation, it raised many problems so it needs to find the real condition of this policy. This research is to find out the power of free schooling education policy implementation in achieving quality of education based national standard at senior high school. The general objective of this research is to describe and evaluate the implementation of free schooling education Policy in achieving quality of education based on national standard. This research used a descriptive and qualitative method which tried to analyze the real phenomenon without any interventions from the researcher; after the data of research has been collected the data is inspected and analyzed. The result of this research shows that the first, the implementation of free schooling policy could not be hoped to serve good education based national education standard. It can be seen from head master stated that 20 % till 35% budget lost because of this policy. Secondly, the policy of free schooling effectively in increasing total of people go to school because 40% till 50% student of High school increased in total each school. The third, the free schooling policy had given bad effect to the parents’ motivation in spending money to invest for their children education. Decreasing of parents’ care to their children education achieved till 30%. It shows that free schooling made parents to give education duty to government totally. Abstrak Secara politik, janji kebijakan sekolah gratis untuk masyarakat memang menggiurkan, namun dalam pelaksanaannya menimbulkan berbagai masalah. Sekolah gratis di lapangan banyak tidak seperti yang dijanjikan dan perlu ditemukan kondisi sesungguhnya. Penelitian ini menginvestigasi dan mengevaluasi implementasi kebijakan sekolah gratis dalam upaya mencapai Standar Nasional Pendidikan. Penelitian ini menggunakan metode deskriptif evaluatif untuk mengungkap fenomena implementasi kebijakan sekolah gratis tanpa intervensi peneliti. Setelah data dianalisis, hasil penelitian menunjukkan bahwa: pertama, penerapan kebijakan sekolah gratis tidak dapat diharapkan dalam upaya sekolah menjadi berkualitas berdasarkan Standar Nasional Pendidikan (SNP). Hal ini terlihat dari hasil wawancara dan angket yang menunjukkan 20 % hingga 35% anggaran biaya operasional sekolah tidak terpenuhi. Kedua, kebijakan sekolah gratis terbukti efektif dalam meningkatkan kuantitas siswa sekolah, data menunjukkan 49.28% siswa bertambah pasca penerapan kebijakan ini. Ketiga, motivasi siswa dan orang tua untuk mendukung peningkatan kualitas pendidikan menjadi rendah, hanya 30% orang tua menunjukkan motivasi investasi dalam pendidikan, selebihnya terpapar dampak gratis bermental serba gratis dan menjadi peminta.